Estimation of microtexture region orientation distribution functions using eddy current data. (7th June 2021) - Homa, Laura; Cherry, Matthew; Wertz, John
Abstract: Microtexture regions (MTRs) within titanium alloys are collections of grains with similar crystallographic orientation. The presence of MTRs can be detrimental to the life of an engine component; as such, a method to detect and characterize MTRs is needed. One potential technique to characterize MTRs is eddy current (EC) testing, which is a nondestructive evaluation technique that is sensitive to the changes in local conductivity due to changes in local crystallographic orientation. While it has been established in the literature that EC methods are sensitive to the presence of MTRs, work has begun only recently to determine the ability of EC to characterize MTRs. In this work, we develop an algorithm to estimate the orientation distribution function of an MTR of interest using EC data. The method relies on an application of the central limit theorem, and the inverse problem is solved in using a likelihood-free technique. Numerical examples using simulated EC data are shown.